Prinsip Proporsionalitas dalam Putusan Mahkamah Konstitusi (Studi Perbandingan di Indonesia dan Jerman) - Irene Angelita Rugian (The Constitutional Court of the Republic of Indonesia, 2021)
The judicial review of UUD 1945 is the authority of the Constitutional Court declared by Article 24C UUD NRI 1945. One of the reasons for judicial review is competiting rights or the constitutional rights of citizens who have been violated through existing laws, so there needs to be an examination of the law these laws. It is also known that some of the judges’ decisions in competiting rights cases only use the interpretation of the constitution without considering the impairment of rights delivered by the applicant in the examination. Thus resulting in a decision stating that the law does not conflict with the constitution. This hurts citizens who feel their rights have been violated. A balance is needed between the public interest and the constitutional rights of citizens. The counterweight can use the principle of proportionality. The principle of proportionality is needed by the constitutional judge in his consideration when faced with a case of competiting rights. But unfortunately, this principle is not always used when faced with competiting rights, and the principle was not developed by Constitutional Court judges. In this paper the problem to be answered is first the history of the principle of proportionality, secondly the comparison of the use of the principle of proportionality in constitutional justice in Germany and Indonesia. The problem was answered using normative legal research methods. The main material is the decision of the Constitutional Court and supporting materials in the form of books and journals. The conclusion in this paper is the need to use the principle of proportionality in dealing with competiting rights cases in the Constitutional Court. So it is necessary to immediately develop the principle of proportionality and its parameters.